1975
DOI: 10.1080/00223980.1975.9915766
|View full text |Cite
|
Sign up to set email alerts
|

Affluence of the Recipient, Value of Donations, and Sharing Behavior in Preschool Children

Abstract: Twenty-eight four-year-old and 28 five- and six-year-old subjects were presented with either poor or rich recipients. The recipients were defined visually with a picture of the type of home they lived in and verbally with a brief story. All subjects were asked to share from 17 units of each of two types of candy, one of low and the other of high value. The subjects assigned poor recipients shared a significantly larger number of units than the subjects assigned rich recipients, and all subjects shared a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 5 publications
1
14
1
Order By: Relevance
“…This is not an unexpected finding since there is a large body of research indicating that children become more generous with age (c/., 6). Contrary to the findings of Zinzer et al (8), when a large number of items were available the children did not donate more of the less preferred object. This finding is somewhat surprising, at least in regard to older children, but there are several plausible explanations: Older children have a greater understanding of what is fair and equitable (5).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is not an unexpected finding since there is a large body of research indicating that children become more generous with age (c/., 6). Contrary to the findings of Zinzer et al (8), when a large number of items were available the children did not donate more of the less preferred object. This finding is somewhat surprising, at least in regard to older children, but there are several plausible explanations: Older children have a greater understanding of what is fair and equitable (5).…”
Section: Discussioncontrasting
confidence: 99%
“…Their system of internalized norms is also superior to that of younger children. It is possible that since the sixth graders did not have any basis for comparison, as they did in the Zinzer et al (8) study, they were giving what they felt was an equitable amount of the money to the "needy children." They may not have been reflecting on the value of the donation but rather on the number of units available.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This surprising finding may have occurred by chance, or it may have been rooted in the use of simple liking measures in most previous studies but trait adjective scales in the current study. A more substantive interpretation draws on findings that young children are socialized at an early age to believe that poor people should be helped (Connell, 1977), are more likely to share with a poor child than with a rich child (Zinser, Perry, & Edgar, 1975), and are more likely than older children to give rewards for performance to a poor child in a situation where poverty is an irrelevant factor (Zinser, Starnes, & Wild, 1991). Being less committed than older children to the belief that a poor man must be lacking in intelligence and/or motivation, first graders in the current study may have felt sorry for him because he lacked the basic necessities of life, viewing him as a nice person deserving of sympathy.…”
Section: Discussionmentioning
confidence: 99%
“…List and Samak (2013) investigated the presence of altruistic or warm glow giving among preschoolers, and concluded that giving is primarily driven by pure altruism at this age. Whether children of this age may recognize neediness in others and discriminate in their sharing accordingly was studied by Zinser, Perry and Edgar (1975). The authors gave children between 4 and 6 years old an opportunity to share candies with an individual whose relative affluence or poverty was indicated by a picture of 8 the type of house they lived in (similar to our study) and a brief story.…”
mentioning
confidence: 88%